8.4 GHz VLBI observations of SN 2004et in NGC 6946 - Marti-Vidal, I.; Marcaide, J.; Alberdi, A.; Guirado, J.; Lara, L.; Prez-Torres, M.; Ros, E.; Argo, Megan; Beswick, R.; Muxlow, T.; Pedlar, A.; Shapiro, I.; et al. (EDP Sciences, 2007)
We report on 8.4 GHz very-long-baseline-interferometry (VLBI) observations of the type II-P supernova SN 2004et in the spiral galaxy NGC 6946, made on 20 February 2005 (151 days after explosion). The Very Large Array (VLA) flux density was 1.23 ± 0.07 mJy, corresponding to an isotropic luminosity at 8.4 GHz of (4.45±0.3) 10 25 erg s-1 Hz-1 and a brightness temperature of (1.3 ± 0.3) 108 K. We also provide an improved source position, accurate to about 0.5 mas in each coordinate. The VLBI image shows a clear asymmetry. From model fitting of the size of the radio emission, we estimate a minimum expansion velocity of 15 700 ± 2000 km s-1. This velocity is more than twice the expected mean expansion velocity estimated from a synchrotron self-absorbed emission model, thus suggesting that synchrotron self-absorption is not relevant for this supernova. With the benefit of an optical spectrum obtained 12 days after explosion, we favor an emission model which consists of two hot spots on an underlying expanding shell of width comparable to that of SN 1993J.